1988
DOI: 10.1159/000461861
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Alanine Aminotransferase Elevation in Healthy Swedish Blood Donors - Mainly Caused by Obesity

Abstract: Five hundred consecutive healthy blood donors were tested for serum alanine aminotransferase (ALT) and 44 (8.8%) had increased levels. Donors with and without raised ALT were compared in several aspects but only weight (expressed as percentage of ideal body weight) and sex differed significantly (119.1 ± 14.5 and 106.3 ± 12.8%, respectively; p<0.001 and males 97.7 and 77.1%, respectively; p<0.01). The 44 donors with raised ALT were followed up and in 13 out of 15 donors with persistently raised ALT without obv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
(30 reference statements)
1
9
0
Order By: Relevance
“…This phenomenon occurs in a high proportion of blood donors followed over time [22,23], and has been shown to bear no relationship to GBV-C/HGV infection [2,16]. Raised ALT levels in blood donors are associated with male gender and increased body weight [24,25], but have not convincingly been shown to be linked to any particular risk behaviour for viral transmission.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon occurs in a high proportion of blood donors followed over time [22,23], and has been shown to bear no relationship to GBV-C/HGV infection [2,16]. Raised ALT levels in blood donors are associated with male gender and increased body weight [24,25], but have not convincingly been shown to be linked to any particular risk behaviour for viral transmission.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in aminotransferases (AST and ALT) in blood plasma is related to, that is among others, liver or skeletal muscle injuries or heart attack (18). Moreover, population studies have shown significant correlations between ALT activity and body weight as well as body mass index (BMI) (27,29,32). Similar correlations in regard to AST were also reported (26,29).…”
mentioning
confidence: 87%
“…Alanine aminotransferase (ALT) activity is the most specific and widely used screening test in the evaluation of hepatic disease. It has been suggested that age, body mass index (BMI), obesity, and serum cholesterol levels influence ALT activity, yet no clear guidelines for changes in ALT activity with age have been constructed 25–28 . The possible association between ALT activity and mortality has not been previously studied in older people.…”
mentioning
confidence: 99%